PERBEDAAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) DENGAN PEMBELAJARAN KONVENSIONAL PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMA N 2 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Gusnita, Herma; Mirna, Tanjung; Sumarni, Sumarni (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research based by low result of economy learner. That cause by some factors, the factors such as method which teacher still used teacher center, the students less involve in teaching learning and value which used result of value not process of value. The goal of this research is for looking different result of learner students used Creative Problem Solving which conventional learning at SMA N 2 Pancung Soal regency of Pesisir Selatan. Kind of this result is experimental of research and interpretation sample technique that used is purposive sampling. Population of all the student grade XI IPS SMA N 2 Pancung Soal regency of Pesisir Selatan which listed in 2013/2014, wheares sample of this research are the students of XI IPS 2 as experimental class and student of XI IPS 3 as control class. Analysis data of technique which use by Z experimental because of data normal distribution and group of data has variation that homogen. The result of experiment showed average result of learning experiment class is 82,28, while the average class control is 78,77. Based analisys data which got, Zhitung =2,049 > Ztabel= 1,96 so that the found is Ho regected an Ha accepted. So, that conclude there are different the result students learning used Creative Problem Solving with conventional learning, that learning using Creative Problem Solving the result of learning higher than using conventional learning. This result hoped can benefit for all are the leader for sosialization Creative Problem Solving especially teacher of economic for teacher can applied Creative Problem Solving and for researcher as reference for the next research.